Improving out-of-hours surgical patient care. Issue 7 (13th August 2018) - Hart, Thomas; Samways, Jack William; Kukendrarajah, Kishore; Keenan, Matthew; Chaudhri, Saurabh
Abstract : Purpose: The Royal College of Surgeons recognises patient handover as the point at which patients are collectively at their most vulnerable. Concerns were raised in a London teaching hospital surgical department regarding an unstructured handover system, poor access to relevant clinical information, and inadequate weekend staffing. A quality improvement programme was designed and implemented to respond to these concerns and improve patient safety. The paper aims to discuss these issues. Design/methodology/approach: A structured questionnaire was distributed to staff and results used to construct a diagram outlining the main factors influencing weekend patient safety. This framework was used to design changes, including a new electronic handover tool, regular handover meetings and additional weekend staff. Regular staff training was provided, and success was assessed in a continuous audit cycle with the results fed back to team leaders. Findings: Over a three-month period, the handover meeting recorded an attendance rate consistently above 80 per cent. The electronic handover entries were scored according to seven criteria (correct layout; key information, i.e.: patient location, clinical priority, active issues, resuscitation status, test results and weekend plan), averaging between 42.2 and 92.9 per cent, with progressive improvement seen over the assessment period. Weekend staffing was increased by 50 per cent, allowing a dedicated team to care for stable inpatients and to oversee discharges. Originality/value: This improvement programme delivered lasting and significant change in response to staff concerns. It resulted in a more structured and reliable weekend system and established key mechanisms for dynamic performance feedback.